2020
DOI: 10.1002/chem.202002688
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a ZnII MOF with Multiple Functional Sites for Highly Efficient Fixation of CO2 under Mild Conditions: Combined Experimental and Theoretical Investigation

Abstract: The development of efficienth eterogeneous catalysts suitable for carbon capture and utilization(CCU) under mild conditions is ap romisingstep towards mitigating the growingc oncentration of CO 2 in the atmosphere.H erein, we report the constructiono fahydrogen-bonded 3D framework, {[Zn(hfipbba)(MA)]•3 DMF} n (hfipbba = 4,4'-(hexaflouroisopropylene)bis(benzoic acid)) (HbMOF1)u tilizingZ n II center,apartially fluorinated, long-chain dicarboxylate ligand (hfipbba), anda na mine-rich melamine (MA) coligand.I nte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 112 publications
(16 reference statements)
3
33
0
Order By: Relevance
“…In this regard, MOFs have attracted tremendous interest owing to their modular nature which facilitates the introduction of CO 2philic and catalytically active sites for the simultaneous capture and utilization of carbon dioxide. [44][45][46][47][48][49][50][51][52] Among the various types of MOFs utilized for the chemical fixation of carbon dioxide, N-heterocyclic carbene (NHC)-based MOFs have gained special interest because the NHC sites can act as potential anchoring sites for catalytic metal ions and also provide CO 2 -philicity to the framework. [53][54][55][56] Here, the covalent linkage formed between the carbene site and Ag(I) will be beneficial in preventing the possible leaching of Ag(I) during the catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, MOFs have attracted tremendous interest owing to their modular nature which facilitates the introduction of CO 2philic and catalytically active sites for the simultaneous capture and utilization of carbon dioxide. [44][45][46][47][48][49][50][51][52] Among the various types of MOFs utilized for the chemical fixation of carbon dioxide, N-heterocyclic carbene (NHC)-based MOFs have gained special interest because the NHC sites can act as potential anchoring sites for catalytic metal ions and also provide CO 2 -philicity to the framework. [53][54][55][56] Here, the covalent linkage formed between the carbene site and Ag(I) will be beneficial in preventing the possible leaching of Ag(I) during the catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the catalytic activity of Cu­(II)-MOF was extended for cycloaddition of various epoxides under the optimized conditions of 80 °C, CO 2 pressure of 8 bar for 24 h. The results showed that catalytic conversion of epoxides with a longer alkyl chain length such as 1,2-epoxypropane, 1,2-epoxybutane, and 1,2-epoxyhexane were found to be reduced to 86, 82, and 48%, respectively, with an increase in the alkyl chain length, which is in line with the previously reported literature (Table , Figures S18–S20), whereas allyl glycidyl ether and butyl glycidyl ether were found to undergo respectively 92 and 84% conversions to the corresponding cyclic carbonates, which can be attributed to the electron-withdrawing nature of the epoxides (Table , Figures S21 and S22). ,, It is worth mentioning that the Cu­(II)-MOF acts as a recyclable catalyst for conversion of CO 2 with ECH at relatively mild conditions (Table S4). …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, control experiments in the absence of catalyst or using CltaH 2 or ZnCl 2 as catalysts led to only 13, 15, and 18% product yields, respectively (entries 14–16). Although a clear relationship between the activity and catalyst structure cannot be clearly demonstrated, a superior activity of the compound 4 may eventually be explained by the presence of open metal sites and OH – groups, along with a Lewis acidic character of zinc­(II) centers. …”
Section: Resultsmentioning
confidence: 99%
“…Following a literature background for related coupling reactions between epoxides and carbon dioxide catalyzed by coordination polymers, ,, a possible mechanism for the present 4 / n -Bu 4 NBr catalytic system was proposed (Scheme ). In the step I, there is an activation of an epoxide substrate by the Lewis acidic site (Zn 2+ ) forming an intermediate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation